2005
DOI: 10.1021/ja051336h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Coordination on the Mismatch Tolerance of Ligand-Modified PNA Duplexes

Abstract: Recent studies on metal incorporation in ligand-modified nucleic acids have focused on the effect of metal coordination on the stability of metal-containing duplexes or triplexes and on the metal binding selectivity but did not address the effect of the sequence of the nucleic acid in which the ligands are incorporated. We have introduced 8-hydroxyquinoline Q in 10-mer PNA strands with various sequences and have investigated the properties of the duplexes formed from these strands upon binding of Cu(2+). Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 55 publications
4
58
0
Order By: Relevance
“…[188][189][190][191][192] Furthermore, the creation of synthetic biometallopolymers and metallopolymer-biopolymer conjugates which incorporate biological self-assembling motifs such as peptides offer potential access to metal-functionalized hierarchical structures and represents another intriguing challenge. [180,183,188,190,193] The development of new synthetic approaches is still vital in many areas, particularly if they lead to metallopolymers with controlled architectures or with unprecedented covalent or noncovalent metallosupramolecular structures. As examples, recently developed covalent-or non-covalent condensation polymerizations are of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…[188][189][190][191][192] Furthermore, the creation of synthetic biometallopolymers and metallopolymer-biopolymer conjugates which incorporate biological self-assembling motifs such as peptides offer potential access to metal-functionalized hierarchical structures and represents another intriguing challenge. [180,183,188,190,193] The development of new synthetic approaches is still vital in many areas, particularly if they lead to metallopolymers with controlled architectures or with unprecedented covalent or noncovalent metallosupramolecular structures. As examples, recently developed covalent-or non-covalent condensation polymerizations are of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…150 All together, their results indicated that strong metal-ligand alternative base pairs significantly diminish the importance of Watson-Crick base pairing for the formation of a stable PNA duplex and led to high mismatch tolerance. 150 This principle can be used in the construction of hybrid inorganic-nucleic acid nanostructures. 150 In a similar line of thought, Diederichsen, Meyer and coworkers have reported the insertion of two successive histidines into the central position of various alanyl-PNA oligomers (alanyl-PNAs).…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 96%
“…147 With this in mind, Achim and co-workers have inserted up to three consecutive 8-hydroxyquinoline-(11, Figure 14) or bipyridine (bipy)-modified (12, Figure 14) PNA monomers into PNA oligomers. [147][148][149][150] They then examined in detail the interaction of these oligomers with different metal ions and also the stability of duplexes formed from them. In the case of 12, variable-temperature UV spectroscopy showed that duplexes containing one terminal pair of bipyridine ligands are more stable upon metal binding with Ni 2+ and Cu 2+ than their non-modified counterparts.…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] In an effort to enhance the versatility of insertion of Ru II complexes into PNAs, our group has envisaged an alternative approach involving the preparation of robust Ru II complexes attached to the PNA backbone, which could be then inserted into a specific site within a PNA sequence. In contrast to the previous reports by Achim et al, [34][35][36] who described the synthesis and then incorporation of bipyridineand 8-hydroxyquinoline-containing PNA monomer into a PNA sequence, our aim is to insert the metal complex directly into the PNA sequence. For similar reasons, our approach is also different to that recently described by Gasser, Metzler-Nolte and co-workers who first inserted one or two alkyne-containing PNA monomers into PNA oligomers and then successfully applied "click chemistry" to attach ferrocene to these sequences.…”
Section: Introductionmentioning
confidence: 99%